The decomposition of productivity gap between Estonia and Korea - Jüri Sepp; Uku Varblane (OrdnungsPolitisches Portal (OPO), 2014)
The paper presents a decomposition of productivity gap between South-Korea and Estonia for the year 2006. After presenting stylised facts related to income conver-gence, we apply shift-share analysis to explain the patterns of structural disparities both at aggregated sectoral level and within the manufacturing sector. We propose an extension to conventional shift-share analysis with using relative productivity indi-cators. Decomposition shows that the overall productivity gap is mainly related to the manufacturing sector. The results show that at sectoral view, discrepancies in productivity levels of individual sectors (within-effect) play the dominant role in productivity gap formation, whereas we find some support for the structural-bonus hypothesis within the manufacturing sector. In line with the previous studies, relative-ly high productivity in financial intermediation and real estate sector as a feature of young market economies was confirmed.
Keywords: 330; decomposition; productivity gap; structural change; employment